Goosebumps graphix. 2, Terror trips - Keenan, Sheila; R.L. Stine; Stine, R. L.; Stine, R. L.; Ganter, Amy Kim.; Thompson, Jill, 1966-; Tolagson, Jamie (New York : Graphix, 2007)
Graphic novel adaptations of three of R.L. Stine's Goosebumps books.
One day at HorrorLand / adapted & illustrated by Jill Thompson -- A shocker on Shock Street / adapted & illustrated by Jamie Tolagson -- Deep trouble / adapted & illustrated by Amy Kim Ganter.
"3 ghoulish Graphix tales"--Cover.
Title from spine.
Keywords: Stine, R. L. -- Adaptations -- Comic books, strips, etc; Monsters -- Comic books, strips, etc. -- Fiction; Graphic novels; Horror comic books, strips, etc